Tissue Distribution of NS-49, a Phenethylamine Class α1A-Adrenoceptor Agonist, in Pigmented Rats - Koike, Tomohiro; Kitazumi, Hiroko; Mukai, Hideya (Arzneimittelforschung, 2001)
After a single oral administration of 1 mg/kg of 14C-NS-49 ((R)-(-)-3’-(2-amino-1-hydroxyethyl)-4’-fluoromethanesulfon-anilide hydrochloride, CAS 137431-04-0), the radioactivity distribution in tissues of male pigmented rats was studied and compared with that in male albino rats. One eye of each pigmented rat was divided into melanin-containing structures (uvea, pigmented epithelium and sclera) and others without melanin (cornea and lens), and the radioactivity concentration in each ocular tissue was measured.In all the pigmented rat body tissues tested, maximum radioactivity concentrations (Cmax) were reached within 4 h after administration. At 1 h, the kidney showed the highest concentration (11 times the plasma concentration), followed by the urethra, liver, urinary bladder and lung. Concentrations in the other tissues were similar to or less than the plasma concentration. The radioactivity concentrations in most tissues decreased rapidly, being less than 10 % of the Cmax 24 h after administration. These characteristics of the 14C-NS-49 tissue distribution in the pigmented and albino rats did not differ. In the eye, however, the radioactivity concentration decreased more slowly in the pigmented than in the albino rats. Most of the radioactivity in the eyes of the pigmented rats was present in melanin-containing structures indicating that NS-49 binds to ocular melanin. The radioactivity concentration in the melanin-containing structures reached a maximum 4 h after administration, then decreased as did that for the whole eye with a t1/2,β of 66.8 h.
Keywords: (R)-(-)-3’-(2-Amino-1-hydro-xyethyl)-4’-fluoromethane sulfonanilide hydrochloride; NS-49, concentration in ocular tissues, tissue distribution; Melanin; CAS 137431-04-0